134 Inter-Hospital Transfer of Neurosurgical Patients to a High Volume Tertiary Care Center: Comprehensive Analysis and Opportunities for Process Improvement. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Holland, Christopher Michael; McClure, Evan W.; Howard, Brian M; Samuels, Owen B.; Barrow, Daniel L.
Abstract: INTRODUCTION: Indications for transfer of neurosurgical patients include absence of local or available neurosurgical coverage, subspecialty or interdisciplinary care requirements, and patient or family preference. The transfer of patients to regional centers is expected to increase with further regionalization of medical care. The transfer records of a large tertiary care medical center were explored to identify trends and opportunities to improve the transfer process. METHODS: All consecutive, prospectively documented requests for inter-hospital patient transfer to the adult neurosurgical service of Emory University Hospitals were identified from a centralized transfer center database for a 1-year study period. Data were extracted from the transfer center database and the electronic medical records were reviewed for admitted patients. RESULTS: Transfer requests for neurosurgical care constituted 1323 (14.6%) of the 9087, of which 81.1% of these requests were accepted, and a total of 984 patients (74.4%) arrived at one of our institutions. Patients arrived from 133 unique referring facilities throughout a catchment area of 66 287 square miles. While the median travel time for transfer patients was 36 minutes, the median interval between the request and patient arrival was 4 hours and 2 minutes. The most frequent diagnoses were intracranial hemorrhage (31.8%), subarachnoid hemorrhage (31.2%), and intracranial tumor (15.2%). The overall diagnostic error rate was 10.3%. Following admission, 42.5% of patients underwent neurosurgical intervention. Fifty-seven patients were inappropriately admitted to intensive care and were immediately transitioned to a lower level of care. CONCLUSION: Efficient and appropriate inter-hospital transfer requires a coordinated effort between hospital administration, physicians, and medical staff to make complex decisions that govern this important and costly process. These data suggest numerous opportunities for improvement exist, including improved diagnostic accuracy, patient triage, and resource allocations, as well as more timely and efficient patient transfers.